2007
DOI: 10.1093/icesjms/fsm021
|View full text |Cite
|
Sign up to set email alerts
|

Injury in trapped Dungeness crabs (Cancer magister)

Abstract: Barber J. S., and Cobb, J. S. 2007. Injury in trapped Dungeness crabs (Cancer magister). – ICES Journal of Marine Science, 64: 464–472. Although traps are the most effective fishing equipment used to capture crabs they can also result in indirect damage to target species. We examined the effect of trap-soak time, crab density, and the legal to sublegal size ratio on injury rates to male Dungeness crabs, Cancer magister. Our field results show that injuries increase significantly with increased trap-soak time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Alcock 1993). This observation is further supported by the fact that injuries to trapped Dungeness crabs are independent of size (Barber and Cobb 2007). However, it is also feasible that interactions did occur between sublegal and legal crabs and they were not documented due to the nature of the time-interval recording.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Alcock 1993). This observation is further supported by the fact that injuries to trapped Dungeness crabs are independent of size (Barber and Cobb 2007). However, it is also feasible that interactions did occur between sublegal and legal crabs and they were not documented due to the nature of the time-interval recording.…”
Section: Discussionmentioning
confidence: 82%
“…If this type of behavioural modification occurs with trapped Dungeness crabs, no relationship would be expected between injuries and trap soak time. However, Barber and Cobb (2007) found a positive relationship between injuries and soak time, while a long-term field study of Dungeness crab found an inverse relationship between limb loss and catch rate (Thomas Shirley, S. James Taggart and Jennifer Mondragon unpublished data). This suggests that injury and limb loss may be related to activities other than agonistic interaction, so clustering could still serve to reduce the number of agonistic interactions in traps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, having pots with doors that open on the top of the pot may not allow trapped crabs to escape even after the clasp breaks since the lids are often held closed by encrusting organisms. Crabs in pots (and more specifically small crabs) have an increased probability of being injured as soak time (the time the pot is in the water) increases (Barber and Cobb, 2007). However, preventing crabs from utilizing their pinchers did not decrease in pot mortality, suggesting that cannibalism within pots is not common (Shirley and Shirley, 1988).…”
Section: Ghost Fishingmentioning
confidence: 99%